Metode Latihan Permainan Target untuk Meningkatkan Akurasi Lemparan Penjaga Gawang Siswa SSB Zeroosix U-11 - Pili Alamsyah; Firman Septiadi; Moch Soleh (Universitas Negeri Medan, 2019)
This study aims to determine whether or not there is an effect of the target game training method on the accuracy of the SSB Zeroosix U-11 goal keeper in 2019. The method used in this study is quantitative research. The research design used was one group pretest posttest design. The population in this study were students of ZeroBix SSB City Sukabumi U-11. The research sample of 21 students. Data collection techniques using survey techniques with test and measurement techniques. The data analysis technique used is the t test significance level of 5% (a = 0.05). The results of this study indicate that there is a significant increase in the accuracy of the goal keeper's throw. The target play training method can encourage students to be more active in the training process and improve students' ability to absorb the training material due to creative and varied training methods. In other words the target play training method deserves to be applied in training especially for the goal keeper.